PENERAPAN MODEL PEMBELAJARAN INQUIRY DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN (PPKn): PENERAPAN MODEL PEMBELAJARAN INQUIRY DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN (PPKn) - Cahyono, Cahyono; Sukarliana, Lili; Mulyana, Dadang (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2021)
One of the learning models in the 2013 curriculum is the inquiry learning model, so researchers are interested in finding out the application of the inquiry learning model in developing students' critical thinking skills in Pancasila and Citizenship Education (PPKn) subjects. The aim is to describe the planning, process, student responses, obstacles and efforts of teachers to the application of the inquiry learning model in developing students' critical thinking abilities in Pancasila and Citizenship Education subjects. The theory used by the inquiry learning model according to Komalasari (2017) and critical thinking according to Deswani (in Nana Najmina 2017). Research Method Descriptive study qualitative approach. Data collection techniques include interviews, literature study, and documentation techniques. Respondents of Pancasila and Citizenship Education Teachers and Class XI Students. Sampling was taken by means of Proportionet Stratified Random Sampling and data processing techniques by means of reduction, display, verification, triangulation. The results showed that with the application of the inquiry learning model students could develop critical thinking skills by solving problems. The obstacles faced are generally from the allocation of time, students and the many efforts made by Pancasila and Civics Education teachers. Keywords: Inquary Learning Model, critical thinking, Pancasila and Citizenship Education